An Oxygen‐Insensitive Hydrogen Evolution Catalyst Coated by a Molybdenum‐Based Layer for Overall Water Splitting. Issue 21 (13th April 2017) - Garcia‐Esparza, Angel T.; Shinagawa, Tatsuya; Ould‐Chikh, Samy; Qureshi, Muhammad; Peng, Xuyuan; Wei, Nini; Anjum, Dalaver H.; Clo, Alain; Weng, Tsu‐Chien; Nordlund, Dennis; Sokaras, Dimosthenis; Kubota, Jun; et al.
Abstract: For overall water‐splitting systems, it is essential to establish O2 ‐insensitive cathodes that allow cogeneration of H2 and O2 . An acid‐tolerant electrocatalyst is described, which employs a Mo‐coating on a metal surface to achieve selective H2 evolution in the presence of O2 . In operando X‐ray absorption spectroscopy identified reduced Pt covered with an amorphous molybdenum oxyhydroxide hydrate with a local structural order composed of polyanionic trimeric units of molybdenum(IV). The Mo layer likely hinders O2 gas permeation, impeding contact with active Pt. Photocatalytic overall water splitting proceeded using MoO x /Pt/SrTiO3 with inhibited water formation from H2 and O2, which is the prevailing back reaction on the bare Pt/SrTiO3 photocatalyst. The Mo coating was stable in acidic media for multiple hours of overall water splitting by membraneless electrolysis and photocatalysis. Abstract : Oxygen‐tolerant hydrogen evolution : Molybdenum species inhibit water‐forming reactions on platinum and other metal catalysts. Hydrogen was selectively produced by electro‐ and photocatalytic water splitting in the presence of competing oxygen. In operando characterization revealed an amorphous oxyhydroxide hydrated structure of polyanionic trimeric molybdenum(IV) protecting metallic platinum.